Method for recycling of spent quartz crucibles, products produced and uses thereof
By performing steps such as crushing, screening, acid washing, high-temperature roasting, auto-grinding, scrubbing, and wet screening on waste quartz crucibles, the problem of high processing costs for waste quartz crucibles has been solved, achieving efficient resource utilization and the preparation of high-purity quartz sand, meeting the needs of multiple industries.
Patent Information
- Application Number
- CN202310797093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2043-06-30
AI Technical Summary
In the existing technology, waste quartz crucibles are discarded due to breakage, resulting in high costs for stockpiling or landfilling, and putting pressure on the environment and space, with a lack of environmentally friendly treatment methods.
By crushing, screening, acid washing, high-temperature roasting, auto-grinding, scrubbing, and wet screening of waste quartz crucibles, high-purity cristobalite sand and fused quartz glass sand are prepared respectively, realizing the comprehensive utilization of resources.
This technology enables the efficient resource utilization of waste quartz crucibles, improves the economic benefits of enterprise production, reduces labor costs, and produces high-purity quartz sand of different particle sizes to meet the needs of multiple industries. The SiO2 purity reaches 98% or higher, and the recovery rate reaches 96% or higher.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of solid waste resource recycling, in particular, to a recycling method of waste quartz crucible, and especially to high-purity cristobalite sand or high-purity fused quartz glass sand prepared. BACKGROUND
[0002] The quartz crucible is a quartz glass crucible produced by using high-purity quartz sand with a SiO2 content higher than 99.997%, and is widely used for preparing crystalline silicon products. As a key consumable in the new energy and semiconductor industries, the inner and outer walls of the high-purity quartz crucible will produce crystallization layers, which will cause the quartz crucible to break. In the prior art, the broken quartz crucible is generally discarded and treated by stacking or landfill. The cost of stacking or landfill is not only high, but also brings great pressure to the environment and space. Therefore, there is an urgent need for a more environmentally friendly treatment method. SUMMARY
[0003] In order to solve the above technical problems, the present application aims to provide the following solutions:
[0004] 1. A method for preparing cristobalite sand and fused quartz glass sand from waste quartz crucible, wherein the method comprises the following steps:
[0005] 1) crushing and first screening the waste quartz crucible to collect the first undersize and the first oversize, respectively; and acid washing the first undersize obtained in step 1) to obtain first quartz sand;
[0006] 2) high-temperature roasting the first oversize obtained in step 1) to obtain a mixture material in which the surface crystallization layer containing cristobalite sand is separated from the fused quartz glass sand;
[0007] 3) self-milling and second screening the mixture material obtained in step 2) to obtain first cristobalite sand from the second undersize and first fused quartz glass sand from the second oversize;
[0008] 4) scrubbing the first cristobalite sand obtained in step 3), and collecting the third oversize by wet screening to obtain first high-purity cristobalite sand after treatment, and collecting the third undersize to obtain second high-purity cristobalite sand after treatment.
[0009] 2. A method for preparing cristobalite sand and fused quartz glass sand from waste quartz crucible, wherein the method comprises the following steps:
[0010] 1) crushing and first screening the waste quartz crucible to collect the first undersize and the first oversize, respectively; and acid washing the first undersize obtained in step 1) to obtain first quartz sand;
[0011] 2) subjecting the first oversize obtained in step 1) to a high-temperature roasting treatment to obtain a mixture of the surface crystallization layer containing the cristobalite sand and the fused quartz glass sand separated from each other;
[0012] 3) subjecting the mixture obtained in step 2) to a self-milling and a second screening, taking the first cristobalite sand from the undersize of the second screening, and taking the first fused quartz glass sand from the oversize of the second screening;
[0013] 4) subjecting the first fused quartz glass sand of step 3) to a rubbing and a wet screening to collect the fourth oversize for processing to obtain the first high-purity fused quartz glass sand, and collecting the fourth undersize for processing to obtain the second high-purity fused quartz glass sand.
[0014] 3. A method for preparing cristobalite sand and fused quartz glass sand using a waste quartz crucible, wherein the method comprises the following steps:
[0015] 1) subjecting the waste quartz crucible to a crushing and a first screening to collect the first undersize and the first oversize, respectively; subjecting the first undersize obtained in step 1) to an acid washing to obtain the first quartz sand;
[0016] 2) subjecting the first oversize obtained in step 1) to a high-temperature roasting treatment to obtain a mixture of the surface crystallization layer containing the cristobalite sand and the fused quartz glass sand separated from each other;
[0017] 3) subjecting the mixture obtained in step 2) to a self-milling and a second screening, taking the first cristobalite sand from the undersize of the second screening, and taking the first fused quartz glass sand from the oversize of the second screening;
[0018] 4) subjecting the first cristobalite sand of step 3) to a rubbing and a wet screening to collect the third oversize for processing to obtain the first high-purity cristobalite sand, and collecting the third undersize for processing to obtain the second high-purity cristobalite sand, and subjecting the first fused quartz glass sand of step 3) to a rubbing and a wet screening to collect the fourth oversize for processing to obtain the first high-purity fused quartz glass sand, and collecting the fourth undersize for processing to obtain the second high-purity fused quartz glass sand.
[0019] 4. The method according to any one of items 1 to 3, wherein
[0020] the waste quartz crucible is a quartz crucible used in the production of a crystalline silicon product using the Czochralski method.
[0021] 5. The method according to any one of items 1 to 3, wherein the waste quartz crucible is crushed to a particle size of less than 10 mm by the crushing in step 1).
[0022] Preferably, the crushing in step 1) is performed using a hammer crusher or a roll crusher.
[0023] 6. The method according to any one of items 1 to 3, wherein,
[0024] The first screening is performed using a sieve with a diameter of 0.7 to 0.9 mm, preferably 0.80 to 0.85 mm, further preferably 0.83 mm, preferably the sieve is a square hole sieve or a round hole sieve.
[0025] 7. The method according to any one of items 1 to 3, wherein,
[0026] The roasting treatment in step 2) is performed at a temperature of 300 to 500 °C, preferably for a roasting time of 1 minute or more, preferably for 1 minute to 1 hour, further preferably for 1 minute to 20 minutes.
[0027] 8. The method according to any one of items 1 to 3, wherein,
[0028] Step 2) of the method further comprises water cooling the first undersize after roasting and recovering the mixture after drying, preferably the cooling water is used for the self-milling after impurity removal by precipitation.
[0029] 9. The method according to any one of items 1 to 3, wherein,
[0030] The self-milling in step 3) is selected from dry self-milling or wet self-milling, preferably the self-milling is performed without grinding balls at a rotation speed of 300 to 500 r / min, further preferably the self-milling time is 1 minute or more, further preferably the self-milling is 1 minute to 30 minutes, further preferably the self-milling is 1 minute to 20 minutes.
[0031] 10. The method according to any one of items 1 to 3, wherein,
[0032] The second screening is performed using a sieve with a diameter of 0.1 to 0.2 mm, preferably 0.15 to 0.18 mm, preferably the sieve is a square hole sieve or a round hole sieve.
[0033] 11. The method according to any one of items 1 to 3, wherein,
[0034] The scrubbing in step 4) is performed by ultrasonic scrubbing of the first square quartz sand or the first fused quartz glass sand obtained in step 3), preferably the ultrasonic frequency is 10 to 40 kHz, further preferably the ultrasonic temperature is 20 to 80 °C, further preferably the ultrasonic time is 10 to 20 min,
[0035] Further preferably, the amount of the scrubbing liquid added for the scrubbing is 5 to 10 times the mass of the first square quartz sand or the first fused quartz glass sand,
[0036] Further preferably, the scrubbing liquid for scrubbing the first quartz sand comprises, by mass parts, 1-20 parts of glacial acetic acid and 100-200 parts of water; or the scrubbing liquid for scrubbing the first fused quartz glass sand comprises, by mass parts, 1-20 parts of oxalic acid and 100-200 parts of water.
[0037] 12. The method according to any one of items 1-3, wherein,
[0038] The wet screening in step 4) is screening the scrubbed material using a screen with a diameter of 0.1-0.2 mm, preferably 0.15-0.18 mm, preferably the screen is a square hole screen or a round hole screen.
[0039] 13. The method according to any one of items 1-3, wherein,
[0040] The treatment of the third oversize or undersize or the fourth oversize or undersize after wet screening is washing with ultrapure water until the pH of the washing liquid is 7, and obtaining the first high-purity quartz sand, the second high-purity quartz sand or the first high-purity fused quartz glass sand, the second high-purity fused quartz glass sand by drying.
[0041] 14. The method according to any one of items 1-3, wherein the pickling is performed using a nitric acid solution with a concentration of 0.1-2 mol / L, preferably the volume mass ratio of the amount of nitric acid solution added to the first undersize is 1-6 L / Kg, further preferably the stirring speed of the pickling is 200-500 r / min, and the stirring acid leaching time is 1-3 h.
[0042] 15. The method according to any one of items 1, 3-14, wherein,
[0043] The prepared first high-purity quartz sand has a particle size of less than 0.18 mm, a SiO2 content of 98%-99.9%, a crystal phase content of more than 98%, and a Ba content of less than 15 mg per kg of high-purity quartz sand;
[0044] The prepared second high-purity quartz sand has a particle size of less than 0.18 mm, a SiO2 content of 98%-99.9%, a crystal phase content of more than 98%, and a Ba content of less than 15 mg per kg of high-purity quartz sand;
[0045] The prepared first quartz sand has a particle size of less than 0.83 mm, and an amorphous content of more than 95%;
[0046] The prepared first fused quartz glass sand has a particle size of more than 0.18 mm, and an amorphous content of more than 95%.
[0047] 16. The method of any of clauses 2, 3-14, wherein,
[0048] The first high purity fused quartz glass sand prepared has a particle size greater than 0.18 mm, a SiO2 content of 98-99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0049] The second high purity fused quartz glass sand prepared has a particle size less than 0.18 mm, a SiO2 content of 98-99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0050] The first quartz sand prepared has a particle size less than 0.83 mm, and an amorphous content of more than 95%;
[0051] The first quartz sand prepared has a particle size less than 0.83 mm, and an amorphous content of more than 95%;
[0052] 17. The method of any of clauses 3-14, wherein,
[0053] The first high purity quartz sand prepared has a particle size less than 0.18 mm, a SiO2 content of 98-99.9%, a crystalline content of more than 98%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0054] The second high purity quartz sand prepared has a particle size less than 0.18 mm, a SiO2 content of 98-99.9%, a crystalline content of more than 98%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0055] The first high purity fused quartz glass sand prepared has a particle size greater than 0.18 mm, a SiO2 content of 98-99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0056] The second high purity fused quartz glass sand prepared has a particle size less than 0.18 mm, a SiO2 content of 98-99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand;
[0057] The first quartz sand prepared has a particle size less than 0.83 mm, and an amorphous content of more than 95%;
[0058] 18. A graded quartz sand and fused quartz glass sand, comprising:
[0059] The first high purity quartz sand has a particle size of less than 0.18 mm, a SiO2 content of 98% to 99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg per kg of high purity quartz sand.
[0060] The second high purity quartz sand has a particle size of less than 0.18 mm, a SiO2 content of 98% to 99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg per kg of high purity quartz sand.
[0061] The first quartz sand has a particle size of less than 0.83 mm and an amorphous content of more than 95%.
[0062] The first fused quartz glass sand has a particle size of more than 0.18 mm and an amorphous content of more than 95%.
[0063] 19. The fractionated quartz sand and fused quartz glass sand according to item 18, which is prepared using the method according to any one of items 1, 3 to 14.
[0064] 20. A fractionated quartz sand and fused quartz glass sand, comprising:
[0065] The first high purity fused quartz glass sand has a particle size of more than 0.18 mm, a SiO2 content of 98% to 99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand.
[0066] The second high purity fused quartz glass sand has a particle size of less than 0.18 mm, a SiO2 content of 98% to 99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg per kg of high purity quartz sand.
[0067] The first quartz sand has a particle size of less than 0.83 mm and an amorphous content of more than 95%.
[0068] The first quartz sand has a particle size of less than 0.18 mm and a crystalline phase content of more than 98%.
[0069] 21. The fractionated quartz sand and fused quartz glass sand according to item 20, which is prepared using the method according to any one of items 2, 3 to 14.
[0070] 22. A fractionated quartz sand and fused quartz glass sand, comprising:
[0071] The first high purity quartz sand has a particle size of less than 0.18 mm, a SiO2 content of 98% to 99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg per kg of high purity quartz sand.
[0072] The second high-purity quartz sand has a particle size less than 0.18 mm, a SiO2 content of 98% to 99.9%, a crystal phase content of more than 98%, and a Ba content of less than 15 mg per kg of high-purity quartz sand.
[0073] The first high-purity fused quartz glass sand has a particle size greater than 0.18 mm, a SiO2 content of 98% to 99.9%, a non-crystal content of more than 95%, and a Ba content of less than 15 mg per kg of high-purity quartz sand.
[0074] The second high-purity fused quartz glass sand has a particle size less than 0.18 mm, a SiO2 content of 98% to 99.9%, a non-crystal content of more than 95%, and a Ba content of less than 15 mg per kg of high-purity quartz sand.
[0075] The first quartz sand has a particle size less than 0.83 mm and a non-crystal content of more than 95%.
[0076] 23. The graded quartz sand and fused quartz glass sand according to item 22, which is prepared by the method according to any one of items 3 to 14.
[0077] 24. The use of the graded quartz sand and fused quartz glass sand according to any one of items 18 to 23, wherein the first high-purity quartz sand and the second high-purity quartz sand are used as metallurgical raw materials, the first quartz sand, the first high-purity fused quartz glass sand, and the second high-purity fused quartz glass sand are used as metallurgical additives, for the production of silicon compounds, as a starting material for porcelain and refractory materials, and the first quartz sand and the first quartz sand are used as fillers for construction machinery.
[0078] Inventive effects
[0079] The raw material of the present application is derived from waste quartz crucibles, which is different from the traditional method of preparing high-purity fused quartz glass sand using quartz ore. The present application not only realizes the resource utilization of solid waste, but also improves the economic benefits of enterprise production and saves production costs.
[0080] The present application uses high-temperature stripping of the crystallization layer to reduce the cost of manual work, and the organic impurities attached to the surface can also be removed during the high-temperature process.
[0081] The present application comprehensively utilizes waste quartz crucibles, so that the utilization rate of waste quartz crucibles reaches more than 95%, and high-purity fused quartz glass sand with different particle sizes can be prepared to meet the needs of different industries. At the same time, the crystallization layer is recycled and reused, and can meet the needs of other industries through grinding and screening.
[0082] The high-purity fused quartz glass sand and the high-purity fused quartz glass sand containing quartz produced by the present application can have a SiO2 purity of 98%.
[0083] The purity of the high-purity quartz sand SiO2 produced by the application can reach 98% or above, and the recovery rate can reach 96% or above.
[0084] The purity of the high-purity quartz sand SiO2 produced by the application can reach 98% or above, and the recovery rate can reach 96% or above. Meanwhile, by grading the high-purity quartz sand, the high-purity quartz sand with a particle size less than 0.18 mm can be used as raw material or additive for metallurgy or for producing silicon compounds in the chemical industry. The high-purity fused quartz glass sand with a particle size of 0.18-0.83 mm can be used as a blank for porcelain and refractory materials. The high-purity quartz sand with a particle size greater than 0.83 mm can be used as a filler in construction machinery. BRIEF DESCRIPTION OF DRAWINGS
[0085] Figure 1 Pictures showing waste quartz crucibles are shown;
[0086] Figure 2 Pictures showing waste quartz crucibles at a calcination temperature of 200℃ are shown in A and 2B;
[0087] Figure 3 Pictures showing waste quartz crucibles at a calcination temperature of 300℃ are shown in A and 3B;
[0088] Figure 4 Pictures showing waste quartz crucibles at a calcination temperature of 400℃ are shown in A and 4B;
[0089] Figure 5 Pictures showing waste quartz crucibles at a calcination temperature of 450℃ are shown in A and 5B. DETAILED DESCRIPTION
[0090] The following embodiments of the application are only used to illustrate the specific embodiments of the application, and these embodiments cannot be understood as limiting the application. Any changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principles of the application are equivalent replacement methods and fall within the protection scope of the application.
[0091] The specific embodiments of the application will be described in more detail below with reference to the accompanying drawings. Although specific embodiments of the application are shown in the drawings, it should be understood that the application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the application and to fully convey the scope of the application to those skilled in the art.
[0092] It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting. It is further understood that the use of certain terminology or words within the specification in no way limits the scope of the application to the specific terminology or words but rather is to be interpreted in the context of the specification as a whole.
[0093] As used herein, "substantially free of," with respect to a particular component, is used to denote that the particular component has not been deliberately formulated into the composition and / or is only present as an incidental or trace amount. Thus, the total amount of a particular component resulting from any incidental contamination of the composition is less than 0.05%, preferably less than 0.01%. Most preferably, compositions wherein the amount of a particular component is not detectable by standard analytical methods.
[0094] As used in this specification, "a" or "an" can mean one or more. As used in the claims, the word "a" or "an" when used in conjunction with the word "comprising" can mean one or more than one.
[0095] The term "or" is used in the claims to mean "and / or" unless explicitly indicated to refer to alternatives only or the alternatives are mutually exclusive, although the disclosure supports a definition that refers to only alternatives and "and / or." As used herein, "another" can mean at least a second or more.
[0096] The application provides a method for preparing cristobalite sand and fused quartz glass sand by using waste quartz crucible, wherein the method comprises the following steps: 1) crushing and first screening the waste quartz crucible, collecting the first undersize and the first oversize respectively; acid washing the first undersize obtained in step 1) to obtain first quartz sand; 2) high-temperature calcination treatment is performed on the first oversize obtained in step 1) to obtain a mixture material in which the surface crystallization layer containing cristobalite sand is separated from the fused quartz glass sand; 3) self-milling and second screening are performed on the mixture material obtained in step 2), the second undersize is taken to obtain first cristobalite sand, and the second oversize is taken to obtain first fused quartz glass sand; 4) the first cristobalite sand obtained in step 3) is scrubbed, and wet screening is performed to collect the third oversize for processing to obtain first high-purity cristobalite sand, and the third undersize is collected for processing to obtain second high-purity cristobalite sand.
[0097] This application provides a method for preparing cubic quartz sand and fused silica glass sand using a waste quartz crucible, wherein the method includes the following steps: 1) crushing and first screening the waste quartz crucible, collecting the first undersize and the first oversize respectively; acid washing the first undersize obtained in step 1) to obtain first quartz sand; 2) high-temperature calcining the first oversize obtained in step 1) to obtain a mixture containing a surface crystallization layer of cubic quartz sand and fused silica glass sand separated; 3) auto-grinding and second screening the mixture obtained in step 2), taking the second undersize to obtain first cubic quartz sand, and taking the second oversize to obtain first fused silica glass sand; 4) scrubbing the first fused silica glass sand from step 3), and wet screening to collect the fourth oversize for processing to obtain first high-purity fused silica glass sand, and collecting the fourth undersize for processing to obtain second high-purity fused silica glass sand.
[0098] This application provides a method for preparing cristobalite sand and fused silica glass sand using waste quartz crucibles, wherein the method includes the following steps: 1) crushing and first screening the waste quartz crucibles to collect the first undersize and the first oversize, respectively; acid washing the first undersize obtained in step 1) to obtain first quartz sand; 2) high-temperature calcining the first oversize obtained in step 1) to obtain a mixture containing a surface crystallized layer of cristobalite sand and fused silica glass sand separated; 3) auto-grinding and second screening the mixture obtained in step 2). 4) The first cubic quartz sand is obtained by taking the material under the second sieve, and the first fused silica glass sand is obtained by taking the material over the second sieve; 5) The first cubic quartz sand in step 3) is washed and wet-screened to collect the material over the third sieve for processing to obtain the first high-purity cubic quartz sand, and the second high-purity cubic quartz sand is obtained by collecting the material under the third sieve for processing; 6) The first fused silica glass sand in step 3) is washed and wet-screened to collect the material over the fourth sieve for processing to obtain the first high-purity fused silica glass sand, and the second high-purity fused silica glass sand is obtained by collecting the material under the fourth sieve for processing.
[0099] The method described in this application enables the comprehensive utilization of waste quartz crucibles, achieving a utilization rate of up to 100%.
[0100] In this application, high-purity cristobalite sand refers to high-purity non-metallic raw materials with a certain particle size specification having a cristobalite crystal phase, specifically referring to high-quality quartz raw materials with a silica content of 95.0%, preferably 96.0%, preferably 97.0% or more, or preferably 98.0% or more.
[0101] In this application, high-purity fused silica glass sand refers to high-quality amorphous glass with a silica (e.g., quartz, silica) content of 95.0%, preferably 96.0%, preferably 97.0% or more, or preferably 98.0% or more. Its atomic structure is long-range disordered, and its high operating temperature and low coefficient of thermal expansion are provided by cross-linking of three-dimensional structure.
[0102] In this application, particle size refers to the aperture of a sieve that allows it to pass through during the sieving process. For example, a particle with a particle size greater than 0.83 mm cannot pass through a sieve with a diameter of 0.83 mm and remains as the oversize material, while particles smaller than 0.83 mm can pass through the sieve. In this application, average particle size is a particle size parameter used to characterize the entire powder. It is generally considered that when sieving with a sieve with a diameter of 0.83 mm, the average particle size of the undersize material is less than 0.83 mm, and the average particle size of the oversize material is greater than 0.83 mm.
[0103] In this application, the waste quartz crucible can be derived from waste quartz crucibles generated by any process, such as waste quartz crucibles damaged due to crystallization, cracking and other stresses during the production of crystalline silicon products using the Czochralski method.
[0104] In this application, crushing can be any crushing method conceived by those skilled in the art, not limited to machine crushing or manual crushing. Machine crushing can be performed in any commercially available or self-made mechanical crusher, such as a hammer crusher, jaw crusher, double roll crusher, or cone crusher. For example, a hammer crusher or double roll crusher can be used to crush waste quartz crucibles into particles with a particle size of less than 10 mm. During the crushing process, the particles can be crushed to quartz sand with a particle size of approximately 0.83 mm. Particles smaller than this size are collected because the main force in the crushing process is compression and shearing, and the crusher has a fixed discharge port size, ensuring that the molten quartz layer follows a normal distribution. This results in the particle size distribution of the target material being mainly concentrated between 0.83 mm.
[0105] In this application, sieving involves using a sieve with a certain diameter to collect the fine powder of the crystalline layer that has been stripped and broken during the crushing process. The shape of the sieve is not limited, as long as it fulfills its function; for example, it can be square, round, triangular, or polygonal, or it can be a cylindrical hole, conical hole, shaped hole, spline hole, or other special-shaped hole. In some preferred embodiments of this application, a square or round sieve with a diameter of 0.83 mm or a square or round sieve with a diameter of 0.15–0.18 mm is used.
[0106] In this application, the first undersize obtained in step 1) is acid-washed to obtain the first quartz sand.
[0107] In some specific methods, the acid washing is carried out using a nitric acid solution with a concentration of 0.1–2 mol / L. Preferably, the volume-to-mass ratio of the nitric acid solution added to the first sieved material is 1–6 L / kg. More preferably, the stirring speed during acid washing is 200–500 r / min, and the stirring and acid leaching time is 1–3 h. For example, the concentration of the nitric acid solution can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, etc. / L or any range thereof; the volume mass ratio can be 1L / Kg, 2L / Kg, 3L / Kg, 4L / Kg, 5L / Kg, 6L / Kg or any range thereof; the stirring speed for pickling can be 200r / min, 210r / min, 220r / min, 230r / min, 240r / min, 250r / min, 260r / min, 270r / min, 280r / min, 290r / min, 300r / min, 310r / min, 320r / min, 330r / min, 340r / min, 350r / min, 360r / min, 370r / min, 380r / min, 390r / min, 400r / min or any range thereof; the stirring and pickling time can be 1h, 2h, 3h or any range thereof.
[0108] In this application, sieving involves using a sieve with a certain diameter to collect the fine powder of the crystalline layer that has been stripped and broken during the crushing process. The shape of the sieve is not limited, as long as it fulfills its function; for example, it can be square, round, triangular, or polygonal, or it can be a cylindrical hole, conical hole, shaped hole, spline hole, or other special-shaped hole. In some preferred embodiments of this application, a square or round sieve with a diameter of 0.83 mm or a square or round sieve with a diameter of 0.15–0.18 mm is used.
[0109] In some specific methods, the first screening uses a screen with a diameter of 0.7–0.9 mm, preferably 0.80–0.85 mm, and more preferably 0.83 mm. The screen is preferably a square-hole screen or a round-hole screen. For example, the diameter of the first screening can be any range from 0.7 mm, 0.71 mm, 0.72 mm, 0.73 mm, 0.74 mm, 0.75 mm, 0.76 mm, 0.76 mm, 0.78 mm, 0.79 mm, 0.80 mm, 0.81 mm, 0.82 mm, 0.83 mm, 0.84 mm, 0.85 mm, 0.86 mm, 0.86 mm, 0.88 mm, 0.89 mm, 0.90 mm.
[0110] In some specific methods, the roasting process involves placing the obtained waste quartz crucible granules in a high-temperature roasting furnace for roasting. Step 2) involves roasting at a temperature of 300–500°C, preferably for more than 1 minute, more preferably for 1 minute to 1 hour, and even more preferably for 1 minute to 20 minutes. For example, the roasting temperature can be any range from 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, or between these values; the roasting time can be any range from 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes, or between these values.
[0111] In this application, the high-temperature calcination temperature range is because this temperature can meet the minimum temperature conditions for the cristobalite layer to detach. Since the two phases are different, have different hardness and different volume expansion, the two substances can be separated by high-temperature calcination and then separated by sieving. However, excessively high detachment temperature will increase unnecessary energy consumption.
[0112] In some specific embodiments, step 2) of the method further includes water cooling of the first sieve residue after calcination, and recycling it after drying as the mixture. Preferably, the cooling water is precipitated and purified before being used in the autogenous grinding process. After removal, it is quickly placed in water for cooling, and hot air is recovered for use as preheating of the granules / hot water is precipitated and purified before being used as water for wet autogenous grinding.
[0113] In some specific methods, the self-grinding in step 3) is selected from dry self-grinding or wet self-grinding. Preferably, the self-grinding is performed without grinding balls at a rotational speed of 300-500 r / min. More preferably, the self-grinding time is more than 1 minute, more preferably 1 minute to 30 minutes, and even more preferably 1 minute to 20 minutes. For example, the rotational speed of the self-grinding can be 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, 460 r / min, 470 r / min, 480 r / min, 4... 90 r / min, 500 r / min or any range thereof; the self-wearing time can be 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes, 30 minutes or any range thereof.
[0114] In this application, auto-grinding can be divided into dry or wet auto-grinding. Choosing auto-grinding without grinding balls reduces the introduction of impurities due to grinding ball wear. Furthermore, since the grinding balls are spherical, the abrasive force generated during high-speed rotation is not conducive to the dissociation of high-hardness materials. The samples themselves have varying shapes, and the collision of these irregular structures at high speeds causes the material to preferentially break from stress concentration areas. Since the stress points of this material are concentrated in air bubbles, the material will break along the bubble edges, resulting in a better grinding effect. Simultaneously, since the target materials in this application are cristobalite crystallized layers and fused quartz, which have significant differences in hardness and brittleness, choosing an auto-grinding process allows the high-hardness fused quartz to selectively grind the low-hardness cristobalite crystallized layers, preferentially grinding the cristobalite crystallized layer sample to a finer particle size, facilitating subsequent processing.
[0115] In this application, the dry autogenous grinding uses a stirred tank with a rotation speed of 300–500 r / min and an autogenous grinding time of 1–15 min. The purpose of selecting this range for dry autogenous grinding is to satisfy the selective grinding effect while avoiding excessive grinding time that would reduce the yield of molten quartz on the screen.
[0116] In this application, the wet autogenous grinding process uses a stirred tank with a rotation speed of 300–500 r / min and a grinding time of 10–30 min. Tap water is used for the autogenous grinding. The purpose of using tap water for the autogenous grinding is to satisfy the selective grinding function while avoiding excessive grinding time that would reduce the yield of molten quartz on the screen.
[0117] In some specific methods, the second screening is performed using a screen with a diameter of 0.1 to 0.2 mm, preferably 0.15 to 0.18 mm, and preferably the screen is a square hole screen or a round hole screen; for example, the diameter can be 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.2 mm or any range therebetween.
[0118] In this application, the wiping method described is any wiping method well known to those skilled in the art, as long as the purpose is achieved. The wiping method can be ultrasonic wiping, mechanical wiping, or other wiping methods. Those skilled in the art can select the wiping parameters according to the actual situation, as long as the purpose is achieved.
[0119] In some specific embodiments, the scrubbing in step 4) involves ultrasonic scrubbing of the first cubic quartz sand or the first fused silica glass sand obtained in step 3). Preferably, the ultrasonic frequency is 10–40 kHz, more preferably the ultrasonic temperature is 20–80 °C, and more preferably the ultrasonic time is 10–20 min. For example, the ultrasonic frequency can be 10 kHz, 11 kHz, 12 kHz, 13 kHz, 14 kHz, 15 kHz, 16 kHz, 17 kHz, 18 kHz, 19 kHz, 20 kHz, 21 kHz, 22 kHz, 23 kHz, 24 kHz, 25 kHz, 26 kHz, 27 kHz, or 28 kHz. The ultrasonic frequency can be any range of Hz, 29kHz, 30kHz, 31kHz, 32kHz, 33kHz, 34kHz, 35kHz, 36kHz, 37kHz, 38kHz, 39kHz, 40kHz or above; the ultrasonic temperature can be any range of 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃ or above; the ultrasonic time can be any range of 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min or above.
[0120] In this application, the selection of the ultrasonic frequency and temperature in step 4) is based on relevant experiments and consideration of industrial feasibility. Scrubbing has a preliminary purification effect, removing impurities introduced during the grinding process or impurities carried by the material itself. Ultrasound can remove suspended impurities and dust. Simultaneous scrubbing and ultrasonic cleaning can achieve better removal results. The use of glacial acetic acid is intended to reduce environmental pollution by employing a weak organic acid, and also because glacial acetic acid has a dissolving effect on iron, calcium, barium, etc., thus providing a certain degree of impurity removal.
[0121] In some specific methods, the amount of scrubbing fluid added is 5 to 10 times the mass of the first cubic quartz sand or the first fused quartz glass sand, for example, it can be 5 times, 6 times, 7 times, 8 times, 9 times, 10 times or any range therebetween.
[0122] In this application, the acid medium used in the wiping solution is not limited in any way and can be a weak acid, such as glacial acetic acid, oxalic acid, ascorbic acid, citric acid, hydrosulfuric acid, hydrogen cyanide, hydrofluoric acid, phosphoric acid, boric acid, formic acid or other weak acids.
[0123] In some specific methods, the scrubbing solution used to scrub the first cubic quartz sand comprises, by weight, 1-20 parts glacial acetic acid and 100-200 parts water; for example, the glacial acetic acid can be any range from 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, or any other range thereof; the water can be any range from 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts, or any other range thereof. The range is specified; or the scrubbing liquid used to scrub the first fused silica glass sand comprises, by weight, 1-20 parts oxalic acid and 100-200 parts water; for example, the oxalic acid can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or any range thereof; the water can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts or any range thereof.
[0124] The choice of scrubbing solution should meet the scrubbing requirements while being more cost-effective and avoiding waste caused by excessive glacial acetic acid that is difficult to dissolve. The amount of glacial acetic acid used can vary depending on the amount of material and the content of impurities.
[0125] In some specific methods, the wet screening in step 4) involves screening the washed material using a screen with a diameter of 0.1–0.2 mm, preferably 0.15–0.18 mm. For example, the screen can be any range from 0.1 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm, 0.2 mm, or the range thereof. Preferably, the screen is a square-hole screen or a round-hole screen.
[0126] In some specific methods, the treatment of the third sieve oversize, third sieve undersize, or fourth sieve oversize and fourth sieve undersize after wet sieving refers to washing with ultrapure water until the pH of the rinsing solution is 7; and then drying to obtain first high-purity cristobalite, second high-purity cristobalite, or first high-purity fused silica glass sand and second high-purity fused silica glass sand.
[0127] In a method for preparing cristobalite sand and fused silica glass sand using waste quartz crucibles, the first high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, a SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the second high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, a SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the first quartz sand prepared has a particle size of less than 0.83 mm and an amorphous content of over 95%; the first fused silica glass sand prepared has a particle size of greater than 0.18 mm and an amorphous content of over 95%.
[0128] In a method for preparing cristobalite sand and fused silica glass sand using waste quartz crucibles, the first high-purity fused silica glass sand prepared has a particle size greater than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the second high-purity fused silica glass sand prepared has a particle size less than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the first quartz sand prepared has a particle size less than 0.83 mm and an amorphous content of over 95%; the first cristobalite sand prepared has a particle size less than 0.18 mm and a crystalline phase content of over 98%.
[0129] In a method for preparing cristobalite sand and fused silica glass sand using waste quartz crucibles, the first high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the second high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; the prepared... The first high-purity fused silica glass sand has a particle size greater than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The second high-purity fused silica glass sand has a particle size less than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first quartz sand has a particle size less than 0.83 mm and an amorphous content of over 95%.
[0130] This application provides graded cristobalite sand and fused silica glass sand, comprising: a first high-purity cristobalite sand with a particle size less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg; a second high-purity cristobalite sand with a particle size less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg; the first cristobalite sand with a particle size less than 0.83 mm and an amorphous content of over 95%; and a first fused silica glass sand with a particle size greater than 0.18 mm and an amorphous content of over 95%. Preferably, it is prepared using a method for preparing cristobalite sand and fused silica glass sand using a waste quartz crucible.
[0131] This application provides graded cristobalite sand and fused silica glass sand, comprising: a first high-purity fused silica glass sand with a particle size greater than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; a second high-purity fused silica glass sand with a particle size less than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; a first cristobalite sand with a particle size less than 0.83 mm and an amorphous content of over 95%; and a first cristobalite sand with a particle size less than 0.18 mm and a crystalline phase content of over 98%. Preferably, it is prepared using a method for preparing cristobalite sand and fused silica glass sand using a waste quartz crucible.
[0132] This application provides graded cristobalite sand and fused silica glass sand, comprising: a first high-purity cristobalite sand with a particle size less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; a second high-purity cristobalite sand with a particle size less than 0.18 mm, an SiO2 content of 98%–99.9%, a crystalline phase content of over 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand; and a first high-purity fused silica glass sand. The first type of high-purity high-purity fused silica glass sand has a particle size greater than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg. The second type of high-purity fused silica glass sand has a particle size less than 0.18 mm, a SiO2 content of 98%–99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg. The third type of high-purity quartz sand has a particle size less than 0.83 mm and an amorphous content of over 95%. Preferably, it is prepared using a method that utilizes waste quartz crucibles to prepare cristobalite sand and fused silica glass sand.
[0133] In this application, the proportion of crystalline phases in the obtained cristobalite sand and fused silica glass sand is detected using an X-ray diffractometer, which can be performed by those skilled in the art based on the instrument's instruction manual.
[0134] In this application, the proportion of amorphous phase in the obtained cristobalite sand and fused silica glass sand is detected by X-ray diffraction, which can be performed by those skilled in the art based on the instrument's instruction manual.
[0135] In this application, the content of each element in cristobalite sand and fused silica glass sand is determined by ICP-OES method. Of course, other methods known to those skilled in the art can also be used.
[0136] This application provides the uses of the above-mentioned graded cubic quartz sand and fused silica glass sand, wherein the first high-purity cubic quartz sand and the second high-purity cubic quartz sand are used as metallurgical raw materials, as metallurgical additives for the first cubic quartz sand, the first high-purity fused silica glass sand and the second high-purity fused silica glass sand, for the production of silicon compounds, as raw materials for ceramics and refractory materials, and as fillers for construction machinery.
[0137] The method described in this application can make full use of waste quartz crucibles and recover more than 95% of the components of waste quartz crucibles, truly turning waste into treasure and achieving full green recycling.
[0138] Example
[0139] This application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. Reagents or instruments used, unless otherwise specified, are all commercially available conventional reagent products.
[0140] High-temperature roasting experiment
[0141] In high-temperature calcination experiments, for discarded quartz crucibles, such as... Figure 1 As shown, numerous experiments were conducted when designing the high-temperature roasting temperature. Specifically: the selected waste quartz crucibles were mainly composed of fused quartz with a crystalline layer on the outer wall, the main component of which was cristobalite phase. First, the waste quartz crucibles were placed in a jaw crusher, crushing most of them to within 10mm. Then, they were further crushed using a roller crusher, and the material that did not pass through a 0.83mm diameter square or round hole sieve during the crushing process was collected, resulting in fine powder of the crystalline layer from the waste quartz crucibles with a particle size greater than 0.83mm. This fine powder was then placed in a high-temperature roasting kiln for roasting at 200℃ for 20 minutes. After roasting, it was quickly removed and poured into cooling water for cooling. The applicant found that when the high-temperature roasting temperature was 200℃, the crystalline layer and fused quartz were not ultimately separated, as shown in the following example. Figure 2 As shown; Figure 2 A indicates that the furnace operates at 200℃ and is held at that temperature for 20 minutes. Figure 2 B indicates that the crystallized layer of the waste quartz crucible was not separated from the molten quartz after being held at 200℃ for 20 minutes.
[0142] Similarly, the applicant found that when the high-temperature calcination was 300°C, the crystalline layer and the fused quartz were ultimately not separated, such as... Figure 3 As shown; Figure 3 A indicates that the furnace operates at 300℃ and is held at that temperature for 20 minutes. Figure 3 B indicates that the crystallized layer of the waste quartz crucible was not separated from the molten quartz after being held at 300℃ for 20 minutes.
[0143] Similarly, the applicant discovered that when the high-temperature calcination was 400°C, the crystalline layer and the fused quartz could eventually be separated, such as... Figure 4 As shown; Figure 4 A indicates that the furnace operates at 400℃ and is held at that temperature for 10 minutes. Figure 4 B indicates that the crystallized layer of the waste quartz crucible separates from the molten quartz after holding at 400℃ for 10 minutes.
[0144] Similarly, the applicant discovered that when the high-temperature calcination was 450°C, the crystalline layer and the fused silica could eventually be separated, such as... Figure 5 As shown;Figure 5 A indicates that the furnace operates at 450℃ and is held at that temperature for 5 minutes. Figure 5 B indicates that the crystallized layer of the waste quartz crucible is separated from the molten quartz after holding at 450℃ for 5 minutes.
[0145] Example 1: A method for preparing cristobalite sand and fused quartz glass sand by separating the crystallization layer from a waste quartz crucible, the method comprising the following steps:
[0146] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 1.
[0147] Table 1. Impurity element content (ppm) of discarded quartz crucibles
[0148] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 58.97 48.3 3.13 27.71 9.5 0.34 12.54 20.1 98.13 Fused quartz 47.46 41.1 2.14 25.79 8.54 0.5 17.49 13.04 98.81
[0149] In Table 1 and Tables 2-20 below, the units for elements other than SiO2 are ppm.
[0150] First, the waste quartz crucibles are placed in a jaw crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The material that does not pass through a square or round hole sieve with a diameter of 0.83mm is collected to remove the material that was peeled off during the crushing process, resulting in fine powder of the crystallized layer of the waste quartz crucibles with a particle size greater than 0.83mm.
[0151] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0152] Fine powder from the crystallized layer of waste quartz crucibles with a particle size greater than 0.83 mm was placed in a high-temperature calcining kiln for calcination at 300℃ for 20 minutes. After calcination, the powder was quickly removed and poured into cooling water for cooling. The fine powder from the crystallized layer of the waste quartz crucibles that had been calcined at high temperature was then subjected to dry auto-grinding. 1000g of quartz sand from the waste quartz crucibles was placed in a mixing tank, and the rotation speed was set to 300r / min for 5 minutes. After the auto-grinding time was completed, the powder was passed through a sieve with a diameter of 0.18mm (square or round holes) to enrich the fine powder from the crystallized layer that had been peeled off and ground during the heating, calcination, and auto-grinding processes.
[0153] Part One:
[0154] Take 550g of the sieve material with a diameter less than 0.18mm after auto-grinding, which is the coarse high-purity cristobalite sand. Place the coarse high-purity cristobalite sand in an ultrasonic cleaner, prepare the scrubbing solution, add 200g of oxalic acid and 2000mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse high-purity cristobalite sand. Set the temperature to 60℃, the scrubbing time to 10min, and the ultrasonic power to 10kHz. After ultrasonic cleaning, pass the sand through a square or round hole sieve with a diameter of 0.18mm to enrich the fine powder of the crystallized layer that was peeled off and ground during the heating, roasting and auto-grinding process. Take the sieve material, which is 500g of refined cristobalite sand.
[0155] The refined high-purity quartz sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After drying with hot air, 498g of finished quartz sand was obtained. The finished quartz sand had a SiO2 content of 98.71% and a Ba content of 9.51mg / kg.
[0156] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning and sieving, place it in an acid-resistant reactor, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain quartz sand.
[0157] Part Two: Take 450g of the material remaining on the sieve after auto-grinding, which has a diameter greater than 0.18mm. Place the coarse fused silica glass sand in an ultrasonic cleaner, prepare a scrubbing solution, add 200g of oxalic acid and 2000mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse fused silica glass sand. Set the temperature to 60℃, the scrubbing time to 10min, and the ultrasonic power to 10kHz. After ultrasonic cleaning, pass the sand through a sieve with a diameter of 0.18mm (square or round holes) to enrich the fine powder of the crystallized layer that was peeled off and ground during the heating, calcination, and auto-grinding processes. Take the material remaining on the sieve, which is 447g of refined fused silica glass sand.
[0158] The refined fused silica glass sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 445g of finished fused silica glass sand. The finished fused silica glass sand had a SiO2 content of 98.91% and a Ba content of 11.11mg / kg.
[0159] Take the ultrasonically cleaned sieve undersize material with a diameter less than 0.18 mm, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to the sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0160] The impurity content detected by the ICP-OES method is shown in Table 2.
[0161] Table 2. Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0162] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 30.41 21.5 0.43 17.3 4.47 0.32 12.18 9.51 99.71 Fused quartz 35.98 24.91 0.69 11.43 6.71 0.51 13.44 11.11 98.91
[0163] Example 2: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallization layer from a waste quartz crucible.
[0164] The method includes the following steps:
[0165] The selected waste quartz crucibles were mainly fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 3.
[0166] Table 3. Impurity element content (ppm) of discarded quartz crucibles
[0167] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 43.2 38.13 4.23 30.01 6.37 1.91 13.94 19.71 98.43 Fused quartz 36.7 30.11 2.13 27.71 5.01 1 9.95 10.2 98.87
[0168] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is enriched by passing it through a square or round hole sieve with a diameter of 0.83mm. The material on the sieve is taken to obtain waste quartz crucible sand with a particle size greater than 0.83mm.
[0169] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0170] Fine powder from the crystallized layer of waste quartz crucible with a particle size greater than 0.83 mm was placed in a high-temperature calcining kiln for calcination at a temperature of 320°C for 15 minutes. After calcination, the powder was quickly removed and poured into cooling water to cool down.
[0171] The fine powder of the crystallized layer of the waste quartz crucible that has been calcined at high temperature is subjected to dry auto-grinding. 1000g of the waste quartz crucible quartz sand is placed in a mixing tank, the rotation speed is set to 300r / min, and the auto-grinding time is 10min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is enriched by passing it through a square or round hole sieve with a diameter of 0.18mm.
[0172] Part One:
[0173] The material passing through a sieve with a diameter less than 0.18 mm after auto-grinding is 545 g of coarse high-purity cristobalite sand. The coarse high-purity cristobalite sand is placed in an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of citric acid and 2000 mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse high-purity cristobalite sand. The temperature is set at 65℃, the scrubbing time at 12 min, and the ultrasonic power at 10 kHz. After ultrasonic cleaning, the sand is passed through a sieve with a diameter of 0.18 mm (square or round holes) to concentrate the fine powder of the crystallized layer that was peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve is 543 g of refined high-purity cristobalite sand. The refined high-purity quartz sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 540g of finished quartz sand. The finished quartz sand had a SiO2 content of 98.78% and a Ba content of 9.13mg / kg.
[0174] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0175] Part Two:
[0176] The material remaining on a sieve with a diameter greater than 0.18 mm after auto-grinding is 455 g of coarse fused silica glass sand. The coarse fused silica glass sand is placed in an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of citric acid and 2000 mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse fused silica glass sand. The temperature is set at 65℃, the scrubbing time at 12 min, and the ultrasonic power at 10 kHz. After ultrasonic cleaning, the sand is passed through a sieve with a diameter of 0.18 mm (square or round holes) to collect the fine powder of the crystallized layer that was peeled off and ground during heating, calcination, and auto-grinding. The material remaining on the sieve is 452 g of refined fused silica glass sand. The refined fused silica glass sand is rinsed with ultrapure water until the pH of the rinsing solution is neutral. After hot air drying, 450 g of finished fused silica glass sand is obtained. The high-purity fused silica glass sand has a SiO2 content of 99.15% and a Ba content of 12.52 mg / kg.
[0177] The sieve undersize material with a diameter less than 0.18 mm after ultrasonic cleaning was collected and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L was added while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve undersize material was 1–6 L / kg. The stirring speed was 100–300 r / min, and the acid leaching time was 1–3 h. After the acid leaching reaction, the reaction product was filtered, and the filter residue was washed with ultrapure water until the pH of the washing solution reached 6.5–7. The washed sample was then placed in an oven and dried at 100–120℃ for 6–10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0178] The impurity content detected by the ICP-OES method is shown in Table 4.
[0179] Table 4. Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0180] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 24.98 17.45 0.4 14.07 3.47 0.83 8.14 9.51 98.78 Fused quartz 23.9 17.91 0.4 9.99. 4.41 0.47 9.91 11.11 99.15
[0181] Example 3: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallization layer from a waste quartz crucible.
[0182] The method includes the following steps:
[0183] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 5.
[0184] Table 5. Impurity element content (ppm) of discarded quartz crucibles
[0185] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 47.3 37.13 2.2 23.91 6 0.99 14.88 17.98 98.37 Fused quartz 36.7 32.32 2.4 19.41 4.99 0.99 11.01 11.41 98.79
[0186] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed using a double-roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is then enriched by passing the material through a square or round hole sieve with a diameter of 0.83mm. The material remaining on the sieve is collected to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0187] Fine powder from the crystallization layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed. Undersize with a diameter less than 0.18 mm is placed in an acid-resistant reactor, and a nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution is 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0188] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed in a high-temperature calcining kiln for calcination at a temperature of 400℃ for 10 minutes. After calcination, the powder was quickly removed and poured into cooling water to cool down.
[0189] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to wet auto-grinding. 5000mL of water is added to the stirring tank, the speed is set to 600r / min, and the auto-grinding time is 18min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is enriched by passing it through a square or round hole sieve with a diameter of 0.18mm.
[0190] Part One:
[0191] 570g of coarse high-purity cristobalite sand was obtained by sieving the material with a diameter less than 0.18mm after auto-grinding. The cristobalite sand was then transferred to an ultrasonic cleaner. The coarse high-purity cristobalite sand was placed in the ultrasonic cleaner, and a scrubbing solution was prepared by adding 200g of glacial acetic acid and 2000mL of water to cover the sample. The temperature was set at 80℃, the scrubbing time at 15min, and the ultrasonic power at 20kHz. After ultrasonic cleaning, the sample was passed through a 0.18mm diameter square or round mesh sieve to collect the fine powder of the crystallized layer that had been peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve was obtained as 567g of refined high-purity cristobalite sand. The refined high-purity cristobalite sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After hot air drying, 565g of finished cristobalite sand was obtained. The finished cristobalite sand had a SiO2 content of 99.61% and a Ba content of 8.71mg / kg.
[0192] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0193] Part Two:
[0194] The material remaining on a sieve with a diameter greater than 0.18 mm after auto-grinding was collected as 430 g of coarse fused silica glass sand. The coarse fused silica glass sand was placed in an ultrasonic cleaner. A scrubbing solution was prepared, with 200 g of glacial acetic acid and 2000 mL of water added to cover the sample. The temperature was set at 80℃, the scrubbing time at 15 min, and the ultrasonic power at 20 kHz. After ultrasonic cleaning, the sample was passed through a sieve with square or round holes (0.18 mm diameter) to collect the fine powder of the crystallized layer that had been peeled off and ground during heating, calcination, and auto-grinding. The material remaining on the sieve was collected as 425 g of refined fused silica glass sand. The refined fused silica glass sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After hot air drying, 418 g of finished fused silica glass sand was obtained. The finished fused silica glass sand had a SiO2 content of 99.81% and a Ba content of 11.71 mg / kg.
[0195] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0196] The impurity content detected by the ICP-OES method is shown in Table 6.
[0197] Table 6. Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0198] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 25.31 21.55 0.43 20.07 4.47 0.8 10 8.71 99.61 Fused quartz 23.9 17.91 0.4 9.99. 4.41 0.47 9.91 11.11 99.15
[0199] Example 4: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallization layer from a waste quartz crucible.
[0200] The method includes the following steps:
[0201] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 7.
[0202] Table 7. Impurity element content (ppm) of discarded quartz crucibles
[0203] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 47 32.1 2.12 20.92 5.1 1.02 14.1 16.99 98.66 Fused quartz 35.41 29.74 2 17.41 4.78 0.87 9.01 10 98.81
[0204] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed using a double-roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is then enriched by passing the material through a square or round hole sieve with a diameter of 0.83mm. The material remaining on the sieve is collected to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0205] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0206] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature calcining kiln for calcination at a temperature of 500℃ for 3 minutes. After calcination, it was quickly removed and poured into cooling water to cool down.
[0207] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to dry auto-grinding. 1000g of waste quartz crucible quartz sand is placed in a mixing tank, the rotation speed is set to 300r / min, and the auto-grinding time is 20min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is enriched by passing it through a square or round hole sieve with a diameter of 0.18mm.
[0208] Part One:
[0209] The material passing through a sieve with a diameter less than 0.18 mm after auto-grinding is 570 g of coarse high-purity cristobalite sand. The coarse high-purity cristobalite sand is then subjected to wet auto-grinding. 5000 mL of water is added to a stirring tank, the rotation speed is set to 500 r / min, and the auto-grinding time is 20 min. After the auto-grinding time is completed, the cristobalite sand is transferred to an ultrasonic cleaner. A waste quartz crucible is placed in the ultrasonic cleaner, and a scrubbing solution is prepared by adding 200 g of glacial acetic acid and 2000 mL of water to cover the sample. The temperature is set to 80℃, the scrubbing time is 20 min, and the ultrasonic power is 30 kHz. After ultrasonic cleaning, the sample is passed through a sieve with a 0.18 mm diameter square or round hole to remove the fine powder of the crystallized layer that was peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve is 574 g of refined high-purity cristobalite sand. The refined high-purity quartz sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 570g of finished quartz sand. The finished quartz sand had a SiO2 content of 99.96% and a Ba content of 8.13mg / kg.
[0210] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0211] Part Two:
[0212] Take 420g of the material remaining on the sieve after auto-grinding (with a diameter greater than 0.18mm), which is the coarse fused silica glass sand. Perform wet auto-grinding on the coarse fused silica glass sand by adding 5000mL of water to a stirring tank, setting the rotation speed to 500r / min, and the auto-grinding time to 20min. After the auto-grinding time, transfer the coarse fused silica glass sand to an ultrasonic cleaner. Prepare the scrubbing solution by adding 200g of glacial acetic acid and 2000mL of water, ensuring the sample is submerged. Set the temperature to 80℃, the scrubbing time to 20min, and the ultrasonic power to 30kHz. After ultrasonic cleaning, pass the sand through a 0.18mm diameter square or round hole sieve to remove the fine powder from the crystallized layer that was peeled off and ground during the heating, calcination, and auto-grinding processes. Take the material remaining on the sieve, which is the refined fused silica glass sand, 415g. The refined fused silica glass sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 413g of finished fused silica glass sand. The finished fused silica glass sand had a SiO2 content of 99.98% and a Ba content of 8mg / kg.
[0213] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0214] The impurity content detected by the ICP-OES method is shown in Table 8.
[0215] Table 8. Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0216] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 20.31 19.78 0.37 14.71 2.71 0.51 5 8.13 99.96 Fused quartz 24.9 18.91 0.14 6.19 2.31 0.31 7.1 8 99.98
[0217] Example 5: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallized layer from a waste quartz crucible.
[0218] The method includes the following steps:
[0219] The selected waste quartz crucibles were mainly fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 9.
[0220] Table 9. Impurity element content (ppm) of discarded quartz crucibles
[0221] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 58.2 47.3 3 28 8.95 0.3 9.9 18.1 99.39 Fused quartz 44.7 42.4 1 25.8 8.65 0.5 17.69 11.1 99.85
[0222] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is removed by passing it through a square or round hole sieve with a diameter of 0.83mm. The material on the sieve is taken to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0223] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0224] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature calcining furnace for calcination at a temperature of 300℃ for 20 minutes. After calcination, it was quickly removed and poured into cooling water to cool down.
[0225] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to dry auto-grinding. 1000g of waste quartz crucible quartz glass sand is placed in a stirring tank, the rotation speed is set to 200r / min, and the auto-grinding time is 5min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is removed by using a square or round hole sieve with a diameter of 0.18mm.
[0226] Part One:
[0227] The material remaining on a sieve with a diameter greater than 0.18 mm after auto-grinding is 950 g of coarse fused silica glass sand. The coarse fused silica glass sand is placed in an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of citric acid and 2000 mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse fused silica glass sand. The temperature is set at 60℃, the scrubbing time at 15 min, and the ultrasonic power at 10 kHz. After ultrasonic cleaning, the sand is passed through a sieve with a diameter of 0.18 mm (square or round holes) to remove the fine powder of the crystallized layer that was peeled off and ground during the heating, calcination, and auto-grinding processes. The material remaining on the sieve is 930 g of refined fused silica glass sand. The refined fused silica glass sand is rinsed with ultrapure water until the pH of the rinsing solution is neutral. After hot air drying, 925 g of finished fused silica glass sand is obtained. The finished fused silica glass sand has a SiO2 content of 99.91% and a Ba content of 9.5 mg / kg.
[0228] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0229] Part Two:
[0230] 50g of coarse high-purity cristobalite sand was obtained by sieving the material with a diameter less than 0.18mm after auto-grinding. The coarse high-purity cristobalite sand was placed in an ultrasonic cleaner. A scrubbing solution was prepared by adding 200g of citric acid and 2000mL of water. The amount of scrubbing solution added was 5 times the mass of the coarse high-purity cristobalite sand. The temperature was set at 60℃, the scrubbing time at 15min, and the ultrasonic power at 10kHz. After ultrasonic cleaning, the sand was passed through a sieve with a 0.18mm diameter square or round hole to remove the fine powder of the crystallized layer that had been peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve was obtained as 48g of refined high-purity cristobalite sand. The refined high-purity cristobalite sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After hot air drying, 46g of finished cristobalite sand was obtained. The finished cristobalite sand had a SiO2 content of 99.83% and a Ba content of 14.78mg / kg.
[0231] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0232] The impurity content detected by the ICP-OES method is shown in Table 10.
[0233] Table 10 Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0234] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 35.10 27.5 0.53 20.30 6.45 0.49 13.33 9.50 99.91 Fused quartz 36.98 30.56 1.19 24.61 7.98 0.77 14.92 12.10 99.83
[0235] Example 6: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallization layer from a waste quartz crucible, the method comprising the following steps:
[0236] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 11.
[0237] Table 11 Impurity element content (ppm) of discarded quartz crucibles
[0238] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 52.20 46.13 2.71 28.13 8.55 0.60 10.97 17.45 99.16 Fused quartz 46.70 39.92 1.71 23.78 8.77 0.53 16.95 11.20 99.85
[0239] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed using a double-roll crusher. The fine powder of the crystalline layer that was peeled off during the crushing process is removed by passing the material through a square or round hole sieve with a diameter of 0.83mm. The material remaining on the sieve is collected to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0240] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0241] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature roasting furnace for roasting at a temperature of 300℃ for 15 minutes. After roasting, it was quickly removed and poured into cooling water to cool down.
[0242] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to dry auto-grinding. 1000g of waste quartz crucible quartz glass sand is placed in a stirring tank, the rotation speed is set to 200r / min, and the auto-grinding time is 10min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is removed by using a square or round hole sieve with a diameter of 0.18mm.
[0243] Part One:
[0244] The material remaining on a sieve with a diameter greater than 0.18 mm after auto-grinding is 975 g of coarse fused silica glass sand. The coarse fused silica glass sand is placed in an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of oxalic acid and 2000 mL of water. The amount of scrubbing solution added is 5 times the mass of the coarse fused silica glass sand. The temperature is set at 70℃, the scrubbing time at 15 min, and the ultrasonic power at 10 kHz. After ultrasonic cleaning, the sand is passed through a sieve with a diameter of 0.18 mm (square or round holes) to remove the fine powder of the crystallized layer that was peeled off and ground during the heating, roasting, and auto-grinding processes. The material remaining on the sieve is 955 g of refined fused silica glass sand. The refined fused silica glass sand is rinsed with ultrapure water until the pH of the rinsing solution is neutral. After hot air drying, 950 g of finished fused silica glass sand is obtained. The finished fused silica glass sand has a SiO2 content of 99.93% and a Ba content of 9.11 mg / kg.
[0245] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0246] Part Two:
[0247] 25g of coarse high-purity cristobalite sand was obtained by sieving the material with a diameter less than 0.18mm after auto-grinding. The coarse high-purity cristobalite sand was placed in an ultrasonic cleaner. A scrubbing solution was prepared by adding 200g of oxalic acid and 2000mL of water. The amount of scrubbing solution added was 5 times the mass of the coarse high-purity cristobalite sand. The temperature was set at 70℃, the scrubbing time at 15min, and the ultrasonic power at 10kHz. After ultrasonic cleaning, the sand was passed through a sieve with a diameter of 0.18mm (square or round holes) to remove the fine powder of the crystallized layer that had been peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve was obtained as 23g of refined high-purity cristobalite sand. The refined high-purity cristobalite sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After hot air drying, 22g of finished cristobalite sand was obtained. The finished fused silica glass sand had a SiO2 content of 99.74% and a Ba content of 13.16mg / kg.
[0248] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0249] The impurity content detected by the ICP-OES method is shown in Table 12.
[0250] Table 12 Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0251] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 36.11 25.45 0.48 20.3 5.47 0.47 12.44 9.5 99.93 Fused quartz 37.98 27.7 0.78 21.11 6.98 0.77 13.93 13.16 99.74
[0252] Example 7: A method for preparing cristobalite sand and fused silica glass sand by separating the crystallization layer from a waste quartz crucible, the method comprising the following steps:
[0253] The selected waste quartz crucibles were mainly fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 13.
[0254] Table 13 Impurity element content (ppm) of discarded quartz crucibles
[0255] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 48.2 45.77 3.13 27.91 7.77 1 11.37 18.45 99.17 Fused quartz 44.7 37.44 2.22 24.01 5.34 0.7 17.44 11.2 99.79
[0256] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed using a double-roll crusher. The fine powder of the crystalline layer that was peeled off during the crushing process is removed by passing the material through a square or round hole sieve with a diameter of 0.83mm. The material remaining on the sieve is collected to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0257] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0258] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed in a high-temperature calcining furnace for calcination at 400℃ for 10 minutes. After calcination, it was quickly removed and poured into cooling water for cooling. The waste quartz crucible sand powder after high-temperature calcination was then subjected to wet auto-grinding. 1000g of waste quartz crucible quartz glass sand was placed in a mixing tank, 2000mL of tap water was added, the rotation speed was set to 500r / min, and the auto-grinding time was 15 minutes. After the auto-grinding time was completed, the powder was passed through a sieve with a diameter of 0.18mm (square or round holes) to remove the fine powder of the crystallized layer that had been peeled off and ground during the heating, calcination, and auto-grinding processes.
[0259] Part One:
[0260] The material remaining on a sieve with a diameter greater than 0.18 mm after auto-grinding is 960 g of coarse fused silica glass sand (i.e., the first fused silica glass sand). The coarse fused silica glass sand is placed in an ultrasonic cleaner. A scrubbing solution is prepared, with 200 g of glacial acetic acid and 2000 mL of water added to cover the sample. The temperature is set at 80℃, the scrubbing time at 15 min, and the ultrasonic power at 20 kHz. After ultrasonic cleaning, the sample is passed through a sieve with a 0.18 mm diameter square or round hole to remove the fine powder of the crystallized layer that was peeled off and ground during heating, calcination, and auto-grinding. The material remaining on the sieve is 950 g of refined fused silica glass sand. The refined fused silica glass sand is rinsed with ultrapure water until the pH of the rinsing solution is neutral. After hot air drying, 940 g of finished fused silica glass sand is obtained. The finished fused silica glass sand has a SiO2 content of 99.94% and a Ba content of 10.75 mg / kg.
[0261] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0262] Part Two:
[0263] 40g of the sieve residue with a diameter less than 0.18mm after auto-grinding was obtained as coarse high-purity cristobalite sand (i.e., first-grade cristobalite sand). The coarse high-purity cristobalite sand was placed in an ultrasonic cleaner. A scrubbing solution was prepared, with 200g of glacial acetic acid and 2000mL of water added to cover the sample. The temperature was set at 80℃, the scrubbing time at 15min, and the ultrasonic power at 20kHz. After ultrasonic cleaning, the sample was passed through a sieve with a 0.18mm diameter square or round hole to remove the fine powder from the crystallized layer that had been peeled off and ground during the heating, roasting, and auto-grinding processes. The sieve residue was obtained as 39g of refined high-purity cristobalite sand. The refined high-purity cristobalite sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After hot air drying, 37g of finished cristobalite sand was obtained. The finished cristobalite sand had a SiO2 content of 99.83% and a Ba content of 9.61mg / kg.
[0264] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0265] The impurity content detected by the ICP-OES method is shown in Table 14.
[0266] Table 14 Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0267] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 33.43 20.94 0.5 17.43 3.12 0.51 9.71 10.75 99.94 Fused quartz 29.11 19.51 0.15 18.1 5.41 0.77 10.71 9.61 99.83
[0268] Example 8: A method for preparing cubic quartz sand and fused quartz glass sand by separating the crystallization layer from a waste quartz crucible, the method comprising the following steps:
[0269] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase. The contents of the main impurity elements detected by ICP-OES are shown in Table 15.
[0270] Table 15 Impurity element content (ppm) of discarded quartz crucibles
[0271] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 41.2 40.77 2.51 24.13 5.41 1 12.1 17.3 99.73 Fused quartz 39.7 37.41 1.79 20.43 3.91 0.68 15.44 11.12 99.91
[0272] First, the waste quartz crucibles are placed in a hammer crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is removed by a square or round hole sieve with a diameter of 0.83mm, resulting in waste quartz crucible sand powder with a particle size greater than 0.83mm.
[0273] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0274] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature calcining furnace for calcination at a temperature of 500℃ for 5 minutes. After calcination, it was quickly removed and poured into cooling water to cool down.
[0275] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to dry auto-grinding. 1000g of waste quartz crucible quartz glass sand is placed in a stirring tank, the rotation speed is set to 200r / min, and the auto-grinding time is 15min. After the auto-grinding time is completed, the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process is removed by using a square or round hole sieve with a diameter of 0.18mm.
[0276] Part One:
[0277] The material remaining on the sieve with a diameter greater than 0.18 mm after auto-grinding is 980 g of coarse fused silica glass sand (i.e., the first fused silica glass sand). The coarse fused silica glass sand is then subjected to wet auto-grinding. 5000 mL of water is added to a stirring tank, the rotation speed is set to 500 r / min, and the auto-grinding time is 20 min. After the auto-grinding time is completed, the silica glass sand is transferred to an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of oxalic acid and 2000 mL of water, ensuring the sample is submerged. The temperature is set to 80℃, the scrubbing time is 20 min, and the ultrasonic power is 20 kHz. After ultrasonic cleaning, the sample is passed through a sieve with a diameter of 0.18 mm (square or round holes) to remove the fine powder of the crystalline layer that was peeled off and ground during the heating, calcination, and auto-grinding processes. The material remaining on the sieve is 970 g of refined fused silica glass sand. The refined fused silica glass sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 965g of finished fused silica glass sand. The finished fused silica glass sand had a SiO2 content of 99.98% and a Ba content of 6.73mg / kg.
[0278] Take the sieve undersize material with a diameter of less than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring for acid leaching. The volume-to-mass ratio of nitric acid solution added to sieve undersize material is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0279] Part Two:
[0280] The material passing through a sieve with a diameter less than 0.18 mm after auto-grinding is 21 g of coarse high-purity cristobalite sand. The coarse high-purity cristobalite sand is then subjected to wet auto-grinding. 5000 mL of water is added to a stirring tank, the rotation speed is set to 500 r / min, and the auto-grinding time is 20 min. After the auto-grinding time is completed, the cristobalite sand is transferred to an ultrasonic cleaner. A scrubbing solution is prepared by adding 200 g of oxalic acid and 2000 mL of water to cover the sample. The temperature is set to 80℃, the scrubbing time is 20 min, and the ultrasonic power is 20 kHz. After ultrasonic cleaning, the sand is passed through a sieve with a diameter of 0.18 mm (square or round aperture) to remove the fine powder of the crystalline layer that was peeled off and ground during the heating, roasting, and auto-grinding processes. The material passing through the sieve is 20 g of refined high-purity cristobalite sand. The refined high-purity quartz sand was rinsed with ultrapure water until the pH of the rinsing solution was neutral. After that, it was dried with hot air to obtain 19g of finished quartz sand. The finished quartz sand had a SiO2 content of 99.96% and a Ba content of 9.51mg / kg.
[0281] Take the sieve residue with a diameter greater than 0.18 mm after ultrasonic cleaning, place it in an acid-resistant reaction vessel, and add nitric acid solution with a concentration of 0.1-2 mol / L while stirring. The volume-to-mass ratio of the nitric acid solution added to the sieve residue is 1-6 L / Kg. The stirring speed is 100-300 r / min, and the stirring and acid leaching time is 1-3 h. After the acid leaching reaction, filter the reaction product, and wash the filter residue with ultrapure water until the pH of the washing solution is 6.5-7. Place the washed sample in an oven to dry at a temperature of 100-120℃ for 6-10 h to obtain a high-purity quartz glass sand filter cake containing cristobalite.
[0282] The impurity content detected by the ICP-OES method is shown in Table 16.
[0283] Table 16 Impurity element content (ppm) of cubic quartz sand and fused silica glass sand
[0284] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 29.47 15.91 0.44 15 2.13 0.31 7.52 6.73 99.98 Fused quartz 29.11 19.51 0.15 18.1 5.41 0.77 10.71 9.51 99.96
[0285] Comparative Example 1's method includes the following steps:
[0286] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase, and the contents of the main impurity elements are shown in Table 17 (detected using the ICP-OES method).
[0287] Table 17 Impurity element content (ppm) of discarded quartz crucibles
[0288]
[0289]
[0290] First, the waste quartz crucibles are placed in a jaw crusher to crush most of them to 15mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that is peeled off during the crushing process is collected by passing it through a square or round hole sieve with a diameter of 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand powder with a particle size less than 0.83mm.
[0291] Fine powder of waste quartz crucible sand with a particle size greater than 0.83 mm was placed in a high-temperature calcining furnace for calcination at 200℃ for 60 minutes. After calcination, it was quickly removed and poured into cooling water for cooling. The fine powder of waste quartz crucible sand after high-temperature calcination was then subjected to dry auto-grinding. 500g of waste quartz crucible quartz glass sand was placed in a stirring tank, and the rotation speed was set to 200r / min for auto-grinding time of 5 minutes. After the auto-grinding time was completed, the powder was passed through a 0.18mm diameter square or round hole sieve to collect the fine powder of the crystallized layer that was peeled off and ground during the heating, calcination and auto-grinding process. The powder was then sieved and analyzed. The sieve still contained most of the glass sand, and complete separation of the crystallized layer from the molten quartz was not achieved.
[0292] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0293] Comparative Example 2's method includes the following steps:
[0294] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase, and the contents of the main impurity elements are shown in Table 18 (detected using the ICP-OES method).
[0295] Table 18 Impurity element content (ppm) of discarded quartz crucibles
[0296] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 53.64 43.57 2.78 21.36 5.31 0.44 18.42 16.35 99.47 Fused quartz 42.37 36.59 1.67 23.75 5.96 0.37 16.77 19.67 99.51
[0297] First, the waste quartz crucibles are placed in a jaw crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that is peeled off during the crushing process is collected by passing it through a square or round hole sieve with a diameter of 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand powder with a particle size greater than 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand powder with a particle size less than 0.83mm.
[0298] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature calcining furnace for calcination at a temperature of 400℃ for 10 minutes. After calcination, it was quickly removed and poured into cooling water to cool down.
[0299] The waste quartz crucible sand powder that has been calcined at high temperature was subjected to wet ball milling. 500g of waste quartz crucible sand was placed in a mixing tank, and 100g of agate balls were added. The rotation speed was set to 230r / min and the ball milling time was 15min. After the ball milling time was completed, the fine powder of the crystallized layer that was peeled off and ground during the heating, calcination and self-milling process was collected by passing it through a square or round hole sieve with a diameter of 0.18mm. 347g of fine powder of the crystallized layer was collected.
[0300] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0301] The selected fine powder of the crystallized layer failed to achieve separation between the crystallized layer and the fused silica.
[0302] Comparative Example 3's method includes the following steps:
[0303] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase, and the contents of the main impurity elements are shown in Table 19 (detected using the ICP-OES method).
[0304] Table 19 Impurity element content (ppm) of discarded quartz crucibles
[0305] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 54.5 42.21 2.45 25.4 9.34 0.22 19.43 15.67 99.36 Fused quartz 41.34 45.65 1.73 24.04 5.61 0.36 17.67 17.95 99.55
[0306] First, the waste quartz crucibles are placed in a jaw crusher to crush most of them to 15mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is removed by passing it through a square or round hole sieve with a diameter of 0.83mm, resulting in waste quartz crucible sand powder with a particle size greater than 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand powder with a particle size less than 0.83mm.
[0307] Waste quartz crucible sand powder with a particle size greater than 0.83 mm was placed into a high-temperature calcining furnace for calcination at a temperature of 200℃ for 30 minutes. After calcination, it was quickly removed and poured into cooling water to cool down.
[0308] The waste quartz crucible sand powder that has been calcined at high temperature is subjected to dry auto-grinding. 500g of waste quartz crucible quartz glass sand is placed in a stirring tank, the rotation speed is set to 200r / min, and the auto-grinding time is 5min. After the auto-grinding time is completed, it is passed through a square or round hole sieve with a diameter of 0.18mm to remove the fine powder of the crystallized layer that has been peeled off and ground during the heating, calcination and auto-grinding process. The material on the sieve is 420g of coarse high-purity fused quartz glass sand containing cristobalite; the material under the sieve is 420g of coarse cristobalite sand containing fused quartz glass sand.
[0309] The sieve screen still contains some cristobalite sand, failing to separate the crystallized layer from the fused quartz. The screen also contains some fused cristobalite glass sand, failing to separate the crystallized layer from the cristobalite.
[0310] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0311] Comparative Example 4's method includes the following steps:
[0312] The selected waste quartz crucibles were mainly composed of fused quartz with a crystallized layer on the outer wall. The crystallized layer was mainly composed of cristobalite phase, and the contents of the main impurity elements are shown in Table 20 (detected using the ICP-OES method).
[0313] Table 20 Impurity element content (ppm) of discarded quartz crucibles
[0314] Composition Al Ca Cu Fe K Li Mg Ba SiO2(%) Crystallized layer 53.64 43.57 2.78 21.36 5.31 0.44 18.42 16.35 99.47 Fused quartz Composition Ca Cu Fe Li Mg Ba Crystallized layer Fused quartz Composition Ca Cu Fe Li Mg Ba Crystallized layer Fused quartz Composition Ca Cu Fe Li Mg Ba Crystallized layer Fused quartz Composition Ca Cu Fe Li Mg Ba Crystallized layer Fused quartz Composition Ca Cu Fe Li Mg Ba Crystallized layer Fused quartz 42.37 36.59 1.67 23.75 5.96 0.37 16.77 19.67 99.51
[0315] First, the waste quartz crucibles are placed in a jaw crusher to crush most of them to 10mm. Then, they are further crushed by a double roll crusher. The fine powder of the crystallized layer that was peeled off during the crushing process is removed by passing it through a square or round hole sieve with a diameter of 0.83mm, resulting in waste quartz crucible glass sand with a particle size greater than 0.83mm. The material that passes through the sieve is taken to obtain waste quartz crucible sand fine powder with a particle size less than 0.83mm.
[0316] Waste quartz crucible glass sand with a particle size greater than 0.83 mm was placed in a high-temperature calcining furnace for calcination at a temperature of 400℃ for 10 minutes. After calcination, the sand was quickly removed and poured into cooling water to cool down.
[0317] Waste quartz crucible glass sand was dry-milled. 500g of the waste quartz crucible glass sand was placed in a mixing jar, along with 200g of agate balls. The milling speed was set to 200 rpm for 15 minutes. After milling, the sand was passed through a 0.18mm diameter square or round mesh sieve to remove the fine powder from the crystallized layer that had been peeled off and ground during the heating, roasting, and auto-milling processes. The material remaining on the sieve was 347g of coarse, high-purity fused quartz glass sand containing cristobalite; the material passing through the sieve was 420g of coarse cristobalite sand containing fused quartz glass sand.
[0318] The sieve still contained some cristobalite sand, failing to separate the crystallized layer from the fused silica. The area under the sieve also contained some cristobalite fused silica glass sand, again failing to separate the crystallized layer from the cristobalite. Furthermore, the SiO2 purity of the coarsely processed high-purity fused silica glass sand containing cristobalite was reduced to 98.94%.
[0319] Fine powder from the crystallized layer of waste quartz crucibles with a particle size less than 0.83 mm, i.e., the undersize, is acid-washed and placed in an acid-resistant reactor. A nitric acid solution with a concentration of 0.1–2 mol / L is added while stirring. The volume-to-mass ratio of the nitric acid solution added to the undersize is 1–6 L / kg. The stirring speed is 100–300 r / min, and the acid leaching time is 1–3 h. After the acid leaching reaction, the reaction product is filtered, and the filter residue is washed with ultrapure water until the pH of the washing solution reaches 6.5–7. The washed sample is then placed in an oven and dried at 100–120℃ for 6–10 h to obtain quartz sand.
[0320] Table 21 List of main conditions for Examples 1-8 and Comparative Examples 1-4
[0321]
[0322]
[0323]
[0324] Calculation of the cost of the experimental purification process
[0325] The equipment used in the process of processing waste quartz crucibles is as follows: horizontal fine grinding mill, ultrasonic cleaner / scrubber, jaw crusher, ball mill, vibrating screen, plate and frame filter press, high-temperature furnace and reactor. The cost, processing capacity and power of these equipment can be referenced from the parameters of commonly used equipment on the market.
[0326] The cost of reagents (refer to information on commercially available medicines) is as follows:
[0327] Based on processing 1 ton of waste quartz crucibles per day (the processing capacity of each step varies depending on the yield of the previous step, as shown in Table 45):
[0328] Table 45: Drug Use and Expenses
[0329]
[0330]
[0331] Note: Due to differences in the purity of the selected drugs, the dosage and price of the drugs shown may differ from the actual situation.
[0332] Energy costs are as follows:
[0333] Based on the power references of the aforementioned equipment, and assuming an 8-hour workday, the energy consumption for one operation is approximately 115–145.2 kW. At a price of RMB 1.025 per kilowatt-hour, the daily energy cost is approximately RMB 117.875–148.83. Therefore, using the method described in this application, waste quartz crucibles can be recycled in a very economical and energy-saving manner.
[0334] Although the embodiments of this application have been described above in conjunction with the specific embodiments described, this application is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the teachings of this specification and without departing from the scope of protection of the claims of this application, and these are all within the scope of protection of this application.
Claims
1. A method for preparing cubic quartz sand and fused silica glass sand using waste quartz crucibles, wherein, The waste quartz crucible is a quartz crucible used in the production of crystalline silicon products using the Czochralski method; the main component of the waste quartz crucible is fused quartz, and the inner and outer walls of the waste quartz crucible have a crystallization layer, the main component of which is cristobalite phase; the method includes the following steps: 1) The waste quartz crucible is crushed and screened for the first time, and the first undersize and the first oversize are collected respectively; the first undersize obtained in step 1) is acid washed to obtain the first quartz sand; 2) The material obtained in step 1) is subjected to high-temperature roasting to obtain a mixture containing a surface crystallized layer of cristobalite sand and fused silica glass sand. The roasting is carried out at a temperature of 300~500℃. 3) The mixture obtained in step 2) is subjected to auto-grinding and second screening. The material under the second sieve is used to obtain the first cubic quartz sand, and the material over the second sieve is used to obtain the first fused silica glass sand. 4) The first cubic quartz sand in step 3) is scrubbed and wet-screened. The material on the third sieve is collected and processed to obtain the first high-purity cubic quartz sand. The material under the third sieve is collected and processed to obtain the second high-purity cubic quartz sand.
2. A method for preparing cristobalite sand and fused silica glass sand using waste quartz crucibles, wherein, The waste quartz crucible is a quartz crucible used in the production of crystalline silicon products using the Czochralski method; the main component of the waste quartz crucible is fused quartz, and the inner and outer walls of the waste quartz crucible have a crystallization layer, the main component of which is cristobalite phase; the method includes the following steps: 1) The waste quartz crucible is crushed and screened for the first time, and the first undersize and the first oversize are collected respectively; the first undersize obtained in step 1) is acid washed to obtain the first quartz sand; 2) The material obtained in step 1) is subjected to high-temperature roasting to obtain a mixture containing a surface crystallized layer of cristobalite sand and fused silica glass sand. The roasting is carried out at a temperature of 300~500℃. 3) The mixture obtained in step 2) is subjected to auto-grinding and second screening. The material under the second sieve is used to obtain the first cubic quartz sand, and the material over the second sieve is used to obtain the first fused silica glass sand. 4) The first fused silica glass sand in step 3) is scrubbed and wet-screened. The material above the fourth sieve is collected and processed to obtain the first high-purity fused silica glass sand. The material below the fourth sieve is collected and processed to obtain the second high-purity fused silica glass sand.
3. A method for preparing cubic quartz sand and fused quartz glass sand using waste quartz crucibles, wherein, The waste quartz crucible is a quartz crucible used in the production of crystalline silicon products using the Czochralski method; the main component of the waste quartz crucible is fused quartz, and the inner and outer walls of the waste quartz crucible have a crystallization layer, the main component of which is cristobalite phase; the method includes the following steps: 1) The waste quartz crucible is crushed and screened for the first time, and the first undersize and the first oversize are collected respectively; the first undersize obtained in step 1) is acid washed to obtain the first quartz sand; 2) The material obtained in step 1) is subjected to high-temperature roasting to obtain a mixture containing a surface crystallized layer of cristobalite sand and fused silica glass sand. The roasting is carried out at a temperature of 300~500℃. 3) The mixture obtained in step 2) is subjected to auto-grinding and second screening. The material under the second sieve is used to obtain the first cubic quartz sand, and the material over the second sieve is used to obtain the first fused silica glass sand. 4) The first cubic quartz sand in step 3) is scrubbed and wet-screened to collect the material on the third sieve for processing to obtain the first high-purity cubic quartz sand. The material under the third sieve is collected and processed to obtain the second high-purity cubic quartz sand. The first fused quartz glass sand in step 3) is scrubbed and wet-screened to collect the material on the fourth sieve for processing to obtain the first high-purity fused quartz glass sand. The material under the fourth sieve is collected and processed to obtain the second high-purity fused quartz glass sand.
4. The method according to any one of claims 1 to 3, wherein, The waste quartz crucible is crushed into particles with a particle size of less than 10 mm by the crushing process in step 1).
5. The method according to claim 4, wherein the crushing in step 1) is performed using a hammer crusher or a double roll crusher.
6. The method according to any one of claims 1 to 3, wherein, The first screening is performed using a screen with a diameter of 0.7~0.9mm.
7. The method according to claim 6, wherein, The first screening is performed using a screen with a diameter of 0.80~0.85mm.
8. The method according to claim 6, wherein, The first screening is performed using a sieve with a diameter of 0.83 mm.
9. The method according to claim 6, wherein, The screen is a square-hole screen or a round-hole screen.
10. The method according to any one of claims 1 to 3, wherein, The roasting time should be more than 1 minute.
11. The method according to claim 10, wherein, Roast for 1 minute to 1 hour.
12. The method according to claim 10, wherein, Roast for 1 to 20 minutes.
13. The method according to any one of claims 1 to 3, wherein, Step 2) of the method further includes water cooling of the first undersize material after calcination and recycling it as the mixture after drying.
14. The method according to claim 13, wherein, The cooling water is used for the autogenous grinding process after sedimentation and impurity removal.
15. The method according to any one of claims 1 to 3, wherein, In step 3), the auto-grinding process can be either dry auto-grinding or wet auto-grinding.
16. The method of claim 15, wherein, Auto-grinding is grinding performed without grinding balls at a speed of 300~500 r / min.
17. The method according to claim 15, wherein, The self-grinding time is more than 1 minute.
18. The method according to claim 15, wherein, The self-grinding time is 1 to 30 minutes.
19. The method according to claim 15, wherein, The self-grinding time is 1 to 20 minutes.
20. The method according to any one of claims 1 to 3, wherein, The second screening is performed using a sieve with a diameter of 0.1~0.2mm.
21. The method according to claim 20, wherein, The second screening is performed using a sieve with a diameter of 0.15~0.18mm.
22. The method according to claim 20, wherein, The screen is a square-hole screen or a round-hole screen.
23. The method according to any one of claims 1 to 3, wherein, The scrubbing in step 4) is performed by ultrasonic scrubbing of the first cubic quartz sand or the first fused quartz glass sand obtained in step 3).
24. The method of claim 23, wherein, The ultrasonic frequency is 10~40 kHz.
25. The method according to claim 23, wherein, The ultrasonic temperature is between 20 and 80°C.
26. The method according to claim 23, wherein, The ultrasound time is 10-20 minutes.
27. The method according to claim 23, wherein, The amount of scrubbing fluid added is 5 to 10 times the mass of the first cubic quartz sand or the first fused quartz glass sand.
28. The method according to claim 27, wherein, The scrubbing solution used to scrub the first cubic quartz sand comprises, by weight, 1-20 parts glacial acetic acid and 100-200 parts water; or the scrubbing solution used to scrub the first fused quartz glass sand comprises, by weight, 1-20 parts oxalic acid and 100-200 parts water.
29. The method according to any one of claims 1 to 3, wherein, The wet screening in step 4) involves screening the washed material using a screen with a diameter of 0.1~0.2mm.
30. The method according to claim 29, wherein, Wet screening involves sieving the washed material using a screen with a diameter of 0.15~0.18mm.
31. The method according to claim 29, wherein, The screen is a square-hole screen or a round-hole screen.
32. The method according to any one of claims 1 to 3, wherein, The treatment of the material above the third sieve, the material below the third sieve, or the material above the fourth sieve and the material below the fourth sieve after wet sieving refers to washing with ultrapure water until the pH of the rinsing solution is 7; and then drying to obtain first high-purity cristobalite, second high-purity cristobalite, or first high-purity fused silica glass sand and second high-purity fused silica glass sand.
33. The method according to any one of claims 1 to 3, wherein, The pickling is carried out using a nitric acid solution with a concentration of 0.1~2 mol / L.
34. The method of claim 33, wherein, The volume ratio of the added nitric acid solution to the first sieve undersize is 1~6 L / kg.
35. The method according to claim 33, wherein, The stirring speed for pickling is 200~500 r / min, and the stirring and pickling time is 1~3 h.
36. The method according to any one of claims 1, 3 to 35, wherein, The first high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The prepared second high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first quartz sand prepared has a particle size of less than 0.83 mm and an amorphous content of over 95%. The first fused silica glass sand prepared has a particle size greater than 0.18 mm and an amorphous content of over 95%.
37. The method according to any one of claims 2, 3 to 35, wherein, The first high-purity fused silica glass sand prepared has a particle size greater than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The prepared second high-purity fused silica glass sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first quartz sand prepared has a particle size of less than 0.83 mm and an amorphous content of over 95%. The first cubic quartz sand prepared has a particle size of less than 0.18 mm and a crystalline phase content of over 98%.
38. The method according to any one of claims 3 to 35, wherein, The first high-purity cristobalite sand prepared has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The prepared second high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first high-purity fused silica glass sand prepared has a particle size greater than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The prepared second high-purity fused silica glass sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first quartz sand prepared had a particle size of less than 0.83 mm and an amorphous content of over 95%.
39. A graded cristobalite sand and fused silica glass sand, comprising: The first type of high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The second type of high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first type of quartz sand has a particle size of less than 0.83 mm and an amorphous content of over 95%. The first fused silica glass sand has a particle size greater than 0.18 mm and an amorphous content of over 95%. The graded cristobalite sand and fused silica glass sand are prepared using the method described in any one of claims 1, 3 to 35.
40. A graded cristobalite sand and fused silica glass sand, comprising: The first type of high-purity fused silica glass sand has a particle size greater than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The second type of high-purity fused silica glass sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first type of quartz sand has a particle size of less than 0.83 mm and an amorphous content of over 95%. The first cubic meter of quartz sand has a particle size of less than 0.18 mm and a crystalline phase content of over 98%. The graded cristobalite sand and fused silica glass sand are prepared using the method described in any one of claims 2, 3 to 35.
41. A graded cristobalite sand and fused silica glass sand, comprising: The first type of high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The second type of high-purity cristobalite sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, a crystalline phase content of more than 98%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first type of high-purity fused silica glass sand has a particle size greater than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of over 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The second type of high-purity fused silica glass sand has a particle size of less than 0.18 mm, a SiO2 content of 98%~99.9%, an amorphous content of more than 95%, and a Ba content of less than 15 mg / kg of high-purity cristobalite sand. The first type of quartz sand has a particle size of less than 0.83 mm and an amorphous content of over 95%. The graded cristobalite sand and fused silica glass sand are prepared using the method described in any one of claims 3 to 35.
Citation Information
Patent Citations
Method for preparing ultralow-metallic-element ultrahigh-purity quartz through mixed acid hot-pressing leaching reaction
CN103539133A
Method for preparing cristobalite micropowder from melted quartz crucibles used during polycrystalline silicon ingot casting
CN107324344A
Method for preparing high-purity ultrafine quartz powder by using waste quartz crucible
CN109809411A
